Baroque and mysticism – hypertrophy of thoughts and emotions? (2) - Matuszewski, Krzysztof (Hybris, 2017)
In the stage of illumination, the soul is dying from the longing for the Spouse. It finds the most efficient way of moderating the pain of inevitable temporal separation in contemplative solitude. Since this solitude does not eliminate the distance, the soul craves for death, which promises it a beatifying meeting. It becomes the supreme goal for the soul and is presented by mystics as a fulfilled communication, or unification. The soul tends to it in a desperate trust in God, filled with a desire for self-loss. The soul tries to overcome with love the uncertainty, which shrouds its relation with the hidden God. This love incites in the soul the desire to see here and now, the impossibility of which is overcome by the ecstasy granted by grace. An ineffable inspiration, which allows the soul to communicate with God, is articulated in the mystical communication thanks to the gift of writing (charisma affabilitatis) and successful use of the metaphor.